A SIW Antipodal Vivaldi Array Antenna Design. (21st January 2016) - Suo, Ying; Li, Wei; Chen, Jianzhong
Abstract : A kind of compact SIW (substrate integrated waveguide) Vivaldi array antenna is proposed and analyzed. The antenna consisted of 4 Vivaldi structure radiation elements fed by an equal power divider with SIW technology. The radiation element is composed of antipodal index gradient microstrip lines on both sides of the substrate. The measured reflection coefficient of the array antenna is less than −10 dB from 8.88 GHz to 10.02 GHz. The measured gain of the array antenna is 13.3 dB on 9.5 GHz.